Thermo-Sensitive Alternative Splicing of FLOWERING LOCUS M Is Modulated by Cyclin-Dependent Kinase G2 - Nibau, Candida; Gallemí, Marçal; Dadarou, Despoina; Doonan, John H.; Cavallari, Nicola (Frontiers in Plant Science, 2020)
The ability to sense environmental temperature and to coordinate growth and development accordingly, is critical to the reproductive success of plants. Flowering time is regulated at the level of gene expression by a complex network of factors that integrate environmental and developmental cues. One of the main players, involved in modulating flowering time in response to changes in ambient temperature is FLOWERING LOCUS M (FLM). FLM transcripts can undergo extensive alternative splicing producing multiple variants, of which FLM-β and FLM-δ are the most representative. While FLM-β codes for the flowering repressor FLM protein, translation of FLM-δ has the opposite effect on flowering. Here we show that the cyclin-dependent kinase G2 (CDKG2), together with its cognate cyclin, CYCLYN L1 (CYCL1) affects the alternative splicing of FLM, balancing the levels of FLM-β and FLM-δ across the ambient temperature range. In the absence of the CDKG2/CYCL1 complex, FLM-β expression is reduced while FLM-δ is increased in a temperature dependent manner and these changes are associated with an early flowering phenotype in the cdkg2 mutant lines. In addition, we found that transcript variants retaining the full FLM intron 1 are sequestered in the cell nucleus. Strikingly, FLM intron 1 splicing is also regulated by CDKG2/CYCL1. Our results provide evidence that temperature and CDKs regulate the alternative splicing of FLM, contributing to flowering time definition.